Interferon-λ3 rs12979860 can regulate inflammatory cytokines production in pulmonary fibrosis - Eman Hamdi; Amany A. Bekhit; Aliaa Higazi; Abo Bakr F. Ahmed; Ahmed Hussein Kasem; Mustafa A.M. Najim; Thamir M. Alshammari; Khaled Thabet (Elsevier, 2023)
Pulmonary fibrosis (PF) is the last phase of interstitial lung diseases (ILDs), which are a collection of pulmonary illnesses marked by parenchymal remodeling and scarring. Treatment can only halt the functional decline of the lung, raising the necessity of identifying the basic processes implicated in lung fibrogenesis. The Interferon lambda-3 (IFNL3) gene variant, rs12979860, was determined to be related to an elevated risk of fibrosis in different organs, but the mechanism through which it mediates fibrogenesis is not clear. In the current research, we aim to figure out some of the mechanistic pathways by which IFN-λ3 mediates ILDs. 100 healthy controls and 74 ILD patients were genotyped for IFNL3 rs12979860. Then the mRNA expression of IFNL3 and some other proinflammatory mediators was examined according to genotype in the peripheral blood mononuclear cells (PBMCs) of ILDs patients. The IFNL3 rs12979860 genotype distribution of healthy individuals and ILDs patients was shown to be in Hardy-Weinberg equilibrium (HWE) with a minor allele frequency (MAF) of 0.293 and 0.326, respectively. Furthermore, the CC genotype was demonstrated to be linked to enhanced IFNL3 expression. Also, the CC genotype was linked to an increase in the mRNA expression of TLR4 (P = 0.03) and the inflammatory cytokines IL-1β and TNF-α (P = 0.01 and 0.04, respectively) and had no effect on the NF-kB level (P = 0.3). From these results, we can deduce that IFN-λ3 may mediate tissue fibrosis via increasing the expression of IFN-λ3 itself and other proinflammatory mediators. This stimulates a self-sustaining loop mechanism which includes a reciprocal production of IFN-λ3, TLR4, IL-1β, and TNF-α leading to persistent inflammation and fibrosis.